The Floating Strip Micromegas Detector Versatile Particle Detectors for High-Rate Applications - Bortfeldt, Jonathan (Springer Theses, Recognizing Outstanding Ph.D. Research, 2015)
This book discusses a novel and high-rate-capable micro pattern gaseous detector of the Micromegas (MICRO-MEsh GAS detector) type. It provides a detailed characterization of the performance of Micromegas detectors on the basis of measurements and simulations, along with an in-depth examination of analysis and reconstruction methods. The accurate and efficient detection of minimum ionizing particles in high-rate background environments is demonstrated. The excellent performance determined here for these lightweight detectors will make possible the live medical imaging of a patient during ion-beam treatment.